Reconceptualizing Communication Overload and Building a Theoretical Foundation. Issue 3 (10th March 2017) - Stephens, Keri K.; Mandhana, Dron M.; Kim, JiHye J.; Li, Xiaoqian; Glowacki, Elizabeth M.; Cruz, Ignacio
Abstract: This study reconceptualizes communication overload and builds a theoretical foundation to understand how this phenomenon applies in contemporary life. We build theory by relying on past research and using a Q-method to capture the subjective perspectives of people who experience communication overload. In our refinement of this abstract concept, we identified seven dimensions composing communication overload. The dimensions included: compromising message quality, having many distractions, using many information and communication technologies, pressuring for decisions, feeling responsible to respond, overwhelming with information, and piling up of messages. Our reconceptualization integrates disparate research, links the availability–expectation–pressure pattern to overload, and elaborates on communication quality, quantity, and generalized perceptions of feeling overwhelmed. The resulting formative theoretical model sets the stage for additional theorizing and empirical studies.